INFLUENCE OF UNIVERSITY AUTONOMY ON THE ADMINISTRATION OF PUBLIC UNIVERSITIES IN NORTH-CENTRAL NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
This study investigated the influence of university autonomy on the administration of public universities in North-Central Nigeria. five research questions were raised in line with five specific objectives to guide the study. Five null hypotheses were formulated and tested at 0.05 level of significance. The study adopted a survey research design. The population of the study was 25,353, comprising academic and non-academic staff from public universities in North-Central Nigeria. The sample size of the study was 394 which was determined by the application Taro Yamane’s formula. Proportionate stratified random sampling technique was adopted for the study. Self-structured questionnaire titled ‘Influence of University Autonomy on the Administration of Public Universities Questionnaire” (IUAAPUQ) was used as instrument for data collection. The instrument was validated by five experts from Joseph Sarwuan Tarka University, Makurdi. The Cronbach Reliability Coefficient obtained for the various clusters were 0.65, 0.68,0.79,0.74,0.73 and the overall   reliability coefficient was 0.89, which was considered reliable for the study. Mean and standard deviation were used to answer the research questions while Chi-square of goodness of fit was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that, organisational autonomy, financial autonomy, staffing autonomy, academic autonomy and autonomy of student’s admission have positive significant influence on the administration of public universities in North-Central Nigeria. Based on the findings, it was recommended government should grant public universities organisational, financial, academic. staffing, and students’ admission autonomy to enhance the smooth administration of Public Universities in North-Central Nigeria.
Keywords: Influence; university autonomy; administration; public universities; north-central Nigeria